Victorian Yankees at Queen Victoria's court American encounters with Victoria and Albert - Weintraub, Stanley, 1929- (University of Delaware Press, co-published with the Rowman & Littlefield Publishing Group, Inc., 2011)
"Little seems to have changed since Victoria's day in the instant magnetism of British royalty across the Atlantic; yet for the first generations liberated by revolution, the British Isles and its sovereigns seemed as remote as the Moon. In the young nation, Americans who were little interested in the sons and daughters of their last king, George III, developed a love-hate relationship with Queen Victoria, his granddaughter, that lasted all her sixty-four years on the throne, ending only with her death in the first weeks of the 20th century"--